Hydrodynamical simulations and similarity relations for eruptive mass-loss from massive stars - Owocki, Stanley P.; Schneider, Fabian (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. Motivated by the eruptive mass-loss inferred from Luminous Blue Variable (LBV) stars, we present 1D hydrodynamical simulations of the response from s
Gesehen am 13.03.2019